Evaluation of Behavioral Characteristics After Hearing in Children with Cochlear Implants - Sari, Elif; Aliyeva, Aynur; Bozkurt, Ergül Başaran; Aydın, Çiğdem Yılmaz; Sari, Ferhat; Olgun, Levent (European Journal of Therapeutics, 2023)
Objective: Cochlear implantation (CI) is an electronic device that converts mechanical sound energy into electrical signals and transmits it directly to the cochlea, allowing sound perception. These implants were applied to patients with severe sensorineural hearing loss who did not or had little benefit from the conventional hearing devices. This study aimed to investigate behavioral problems, find related factors, and determine the relationship between behavioral problems and parents’ attitudes in children with CI. Materials and Methods: The investigation involved the participation of fifty individuals, comprising 26 males and 24 females, between 4 and 18 years, with a mean age average of 4±1.56 without any neurological and developmental problems. Inclusion criteria required a minimum of one year post-CI follow-up and a corresponding minimum duration of one year utilizing CI. Achenbach’s Child Behavior Checklist (CBCL) assessed behavioral aspects. Categories of Auditory Performance II (CAP) and The Speech Intelligibility Rating Scale (SIR) scales were employed to evaluate auditory performance and speech intelligibility. Parental attitudes were gauged using the Parent Attitude Research Instrument (PARI). The selection of fifty patients was accomplished through a simple random sampling technique, with no considerations for gender or social status differences during case selection. Results: The patients who applied the CI bilaterally were more successful than the one-sided. The success rate of patients who had comorbidities was statistically significant. Aggressive behavior was less in patients operated on before age 4. There are no differences between the relations of friend circle, art, and sports-interested patients. For CAP II and SIR, there is a moderate statistical significance between the duration of use and CAP. CAP scores were analyzed high in patients who used the device for over six years. There is a moderate statistical significance between CAP and SIR correlation. Our research found a statistically significant decrease in all behavioral scales when comparing preoperative and postoperative scores. Although there was only a non-significant decrease in the delinquent behaviors score, a decrease was still observed. There were significant changes in males but no significant difference based on gender in our study. Conclusion: The findings imply that implementing cochlear implants in younger children might yield even greater advantages. Our research adds to the expanding collection of evidence endorsing CI as a viable therapeutic choice for youngsters with hearing impairments, underscoring the necessity for continued investigations within this domain.